Development of Integrated Biology Learning Modules on Local Potential of Padang Lawas Karamunting Plants (Rhodomyrtus tomentosa) as Biology Teaching Materials - Hafizah, Anni; Febriani, Indayana; S, Irwan (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2022)
This study aims to determine the validity, practicality, and effectiveness of the integrated biology learning module of the local potential of the Karamunting plant (Rhodomyrtus Tomentosa) for learning activities on Plantae material. This study uses Research and Development (R&D) research methods based on the Thiagarajan methodology with four stages, namely define, design, development and disseminate stages. This research was carried out from July-September 2021 with a research sample of 32 students of class X. The results showed that the percentage of the validity of the assessment by material experts was 87%, media experts was 70%, and the practicality test of biology teacher responses (field practitioners) was 92 % and student responses of 92%. Meanwhile, the results of the test scores for the effectiveness of the biology learning module were proven to increase up to 100% and were able to improve student learning mastery. So, it can be concluded that the integrated biology learning module of the local potential of the Karamunting plant (Rhodomyrtus Tomentosa) as a biology teaching material for class X MAS NU Siborong-borong is valid and effective for learning activities.